Spectroscopic and photometric study of two B-type pulsators in eclipsing systems. Issue Volume 9:Issue S301(2013) (18th February 2014) - Drobek, Dominik; Pigulski, Andrzej
Abstract: Pulsating stars in eclipsing binary systems play an important role in asteroseismology. The combination of their spectroscopic and photometric orbital solutions can be used to determine, or at least to constrain, the masses and radii of components. To successfully perform any seismic modelling of a star, one has to identify at least some of the detected modes, which requires precise time-series photometric and spectroscopic observations. This work presents a progress report on the analysis of two β Cephei-type stars in eclipsing binaries: HD 101794 (V916 Cen) and HD 167003 (V4386 Sgr).